2022
DOI: 10.1177/10887679221108872
|View full text |Cite
|
Sign up to set email alerts
|

Female Homicide and the COVID-19 Pandemic in a State of the Northeast Region of Brazil

Abstract: This paper investigates the impact of the COVID-19 pandemic in the time series of female homicides in the state of Pernambuco, Northeast of Brazil. Microdata on lethal violent crimes from the Department of Social Defense from 2015 to 2020 was used. The homicide rates were analyzed using joinpoint regression models. The results showed an upward trend in homicide rates in the Sertão mesoregion and within the 20 to 39 age group in 2020. It is concluded that confinement and social distancing aggravated the violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Another study focusing on 12 of the 27 Brazilian states 2 and looking at data from March and April 2019 and 2020 indicated that in the states surveyed, there was an increase in 22.2% in feminicide cases and 63.3% in homicides with female victims (Fornari et al, 2021; Fórum Brasileiro de Saúde Pública [FBSP], 2020). An increase in the number of femicides during the pandemic in Brazil has also been confirmed by other studies (dos Santos et al, 2022; Montoya Diaz et al, 2022; Okabayashi et al, 2020).…”
Section: The Impact Of Covid-19 On Femicides: a Review Of The Literaturesupporting
confidence: 74%
“…Another study focusing on 12 of the 27 Brazilian states 2 and looking at data from March and April 2019 and 2020 indicated that in the states surveyed, there was an increase in 22.2% in feminicide cases and 63.3% in homicides with female victims (Fornari et al, 2021; Fórum Brasileiro de Saúde Pública [FBSP], 2020). An increase in the number of femicides during the pandemic in Brazil has also been confirmed by other studies (dos Santos et al, 2022; Montoya Diaz et al, 2022; Okabayashi et al, 2020).…”
Section: The Impact Of Covid-19 On Femicides: a Review Of The Literaturesupporting
confidence: 74%
“…The next article in the special issue examines femicide (i.e., homicide of women) in Brazil, filling gaps in our understanding of the global impact of COVID-19 on gender-based violence. Santos (2022) indicated that social distancing and closing of schools, gyms, and non-essential services occurred early in 2020 in Brazil. There was also Federal Legislation passed that attempted to lessen the impact of COVID-19 on women’s experiences of violence by ensuring that cases moved forward and allowing remote assistance.…”
mentioning
confidence: 99%
“…There was also Federal Legislation passed that attempted to lessen the impact of COVID-19 on women’s experiences of violence by ensuring that cases moved forward and allowing remote assistance. Nevertheless, Santos (2022) reported that there were increases in femicides in Northeast Brazil during 2020 and coinciding with the COVID-19 pandemic. Despite decreases in femicides across locations and age groups prior to 2020, significant increases in homicides of women – in some cases greatly exceeding earlier decreases—were identified.…”
mentioning
confidence: 99%